Multimodal quantum metrology in living systems using nitrogen-vacancy centres in diamond nanocrystals - Hart, Jack W.; Knowles, Helena S. (Frontiers in Quantum Science and Technology, 2023)
Nitrogen-vacancy centres in diamond nanocrystals are among the leading candidates for realising nanoscale quantum sensing under ambient conditions. Due to their exceptional electronic spin coherence at room temperature and optical addressability, these solid state spin-based sensors can achieve a wide selection of sensing modalities, including probing temperature, external magnetic and electric field, pressure and as well as the detection of nearby electronic and nuclear spins. In this article, we discuss recent progress made utilizing nanodiamond quantum sensors in living systems and explore both opportunities for future advances and challenges that lie ahead.